Temelji modelov, teorij in prakse zdravstvene nege - McKenna, Hugh P.; Pajnkihar, Majda; Murphy, Fiona A. (2018)
Fundamentals of Nursing Models, Theories and Practice. The textbook presents an overview of knowledge in the field of theories and models of nursing care and their importance for education, research and practice of nursing care. It covers 9 chapters. In the introduction, the importance of theories of nursing science and the importance of their understanding for nursing practice is defined. The following are contents related to the basic forms of knowledge and knowledge in nursing, the development of theories, the importance of theories in the design of new roles of nurses, the characteristics of models and theories, theories and models of interpersonal relations, the choice of theories of practice, the connection of theories and research, and the criteria to describe, analyze and evaluate theories. In each chapter there are learning outcomes, key concepts, and short extracts. Clear and attractive spreadsheets and schemes also contribute to a better understanding of the content, and various reflexive exercises are available to consolidate knowledge. The textbook is intended for future nurses in studying in modern educational programs of nursing, as it provides a concise introduction to understanding the development, application and evaluation of theories of nursing care.
Keywords: science; practice; research; Concept; Theory